Apoptosis mediated chemosensitization of tumor cells to 5-fluorouracil on supplementation of fish oil in experimental colon carcinoma - Isha Rani; Bhoomika Sharma; Sandeep Kumar; Satinder Kaur; Navneet Agnihotri (Tumor Biology)
5-Fluorouracil has been considered as a cornerstone therapy for colorectal cancer; however, it suffers from low therapeutic response rate and severe side effects. Therefore, there is an urgent need to increase the clinical efficacy of 5-fluorouracil. Recently, fish oil rich in n-3 polyunsaturated fatty acids has been reported to chemosensitize tumor cells to anti-cancer drugs. This study is designed to understand the underlying mechanisms of synergistic effect of fish oil and 5-fluorouracil by evaluation of tumor cell–associated markers such as apoptosis and DNA damage. The colon cancer was developed by administration of N,N -dimethylhydrazine dihydrochloride and dextran sulfate sodium salt. Further these animals were treated with 5-fluorouracil, fish oil, or a combination of both. In carcinogen-treated animals, a decrease in DNA damage and apoptotic index was observed. There was also a decrease in the expression of Fas, FasL, caspase 8, and Bax, and an increase in Bcl-2. In contrast, administration of 5-fluorouracil and fish oil as an adjuvant increased both DNA damage and apoptotic index by activation of both extrinsic and intrinsic apoptotic pathways as compared to the other groups. The increased pro-apoptotic effect by synergism of 5-fluorouracil and fish oil may be attributed to the incorporation of n-3 polyunsaturated fatty acids in membrane, which alters membrane fluidity in cancer cells. In conclusion, this study highlights that the induction of apoptotic pathway by fish oil may increase the susceptibility of tumors to chemotherapeutic regimens.